Historical Evolution of the Bhagavad Gītā (Patan Pragya, 2022)
This research article deals with the development of the Bhagavad Gītā in the present form.The study has its relevance to understand the historical origin of the text so that the reader could able to probe its importance in the present context. The article addresses on the research problems concerning to its affiliation with the epic Mahābhārata, the nature of the text in terms of its birth, its authorship and its date of production. Is the Gītā an independent treatise or a part of the epic? Is the text written at a time or it is a developing text? Who wrote it and when it was written? The article seeks answers to the aforementioned research questions by applying the methodological tool of the Marxist concept of historical materialism. The study reveals that the Bhagavad Gītā is found to be a developing text. The scholars are not unanimous regarding to its affiliation with the epic, to its authorship and its date of production.